Knowledge Diffusion through Islamic Architecture: A Bibliometric Analysis - Harande, Yahya Ibrahim (MiddleBelt Journal of Library and Information Science, 2015)
This paper presents an explorative bibliometrics study of Islamic architecture literature. A list of journal articles on the Islamic architecture researches published during 1962-2011 was generated for analysis from ‘Avery Index to Architectural Periodicals.” architectural database. A total of 114 articles by 103 authors were identified. The term Islamic architecture was used for searching the database. Growth of the literature was studied and lotka’s law was also applied to the compiled data. The finding of the study has indicated that the literature of Islamic architecture is currently receiving some interest and attention from the scholars. On the issue of pattern of authorship, single authorship dominates the literature (84.4%). Furthermore, the five-year spreading of the literature has shown that, there is a significant growth of the literature from 1977 forwards. Lotka’s law was found to be in conformity with the literature of Islamic architecture. Scholars and scientists are hereby urged to improve on their collaborative researches in this subject area, this will add to their global visibility and widen the scope of their knowledge sharing.